2023
DOI: 10.3389/fmicb.2023.1117644
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D alleviates non-alcoholic fatty liver disease via restoring gut microbiota and metabolism

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) represents a severe public health problem. Dysbiosis of gut microbiome has been identified as one of the key environmental factors contributing to NAFLD. As an essential nutrition, Vitamin D (VD) plays an important role in regulating gut microbiota based on its receptor (Vitamin D Receptor, VDR) which is highly expressed in the gastrointestinal tract.MethodsRats were fed with HFD (high-fat diet) for 12 weeks. And the rats were treated with VD two times a week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…The role of diet is vital in the development of obesity, diabetes, and allergies, and a HFD is frequently employed to induce obesity in animal models [ 15 , 25 , 26 ]. After a 20-week intervention with a HFD, we observed that rats became obese and experienced a notable increase in both lipid and blood glucose levels, in agreement with previous studies [ 27 ]. Additionally, rats in the HFD group exhibited increased levels of creatinine and urea nitrogen in their peripheral blood.…”
Section: Discussionsupporting
confidence: 92%
“…The role of diet is vital in the development of obesity, diabetes, and allergies, and a HFD is frequently employed to induce obesity in animal models [ 15 , 25 , 26 ]. After a 20-week intervention with a HFD, we observed that rats became obese and experienced a notable increase in both lipid and blood glucose levels, in agreement with previous studies [ 27 ]. Additionally, rats in the HFD group exhibited increased levels of creatinine and urea nitrogen in their peripheral blood.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have shown that VDR improves aging-related MAFLD by positively regulating mitochondrial function [202]. Additionally, the improvement of gut microbes is considered to be another potential mechanism by which vitamin D alleviates highfat diet-induced MAFLD [203]. Overall, the mechanism by which vitamin D works is inextricably linked to other metabolic pathways, and understanding the physiopathology of vitamin D will help unravel the mystery of MAFLD.…”
Section: Vitamin D Metabolism and Mafldmentioning
confidence: 99%
“…Phototherapy-enhanced active vitamin D3 in mice mitigates hepatocyte apoptosis, inflammation, fibrosis, and insulin/leptin resistance caused by a CDAA diet ( 76 ). Additionally, vitamin D treatment curbs MAFLD induced by a high-fat diet (HFD), involving gut microbiota ( 77 ) and metabolic regulation ( 78 ), and modulates lipid metabolism through the PPARa signaling pathway ( 79 ). Vitamin D-regulated miRNAs are implicated in MAFLD pathogenesis, though more research is needed ( 80 ).…”
Section: Vitamins and Mafldmentioning
confidence: 99%